Literasi Digital Guru dan Pendidikan Masa Depan: Studi Fenomenologi pada Guru-guru MTs Mambaul Ihsan Larangan Perreng Pragaan Sumenep - Farhan; Ghozi Mubarok (La-Tahzan: Jurnal Pendidikan Islam, 2026)
In the era of globalization and rapid technological development, digital literacy has become a key competency for educators, including Madrasah Tsanawiyah (MTs) teachers. This study, titled "Teacher Digital Literacy and Future Education: A Phenomenological Study of Teachers at MTs Mambaul Ihsan Larangan Perreng Pragaan Sumenep," aims to explore the understanding, experiences, and challenges faced by teachers in developing digital literacy and their implications for future educational readiness. Although the government has launched various programs to improve teachers' digital competencies, the reality on the ground shows that obstacles persist, such as limited technological facilities, a lack of ongoing training, and disparities in access between regions. This study uses a phenomenological approach to explore the meaning of teachers' experiences in adapting to digital-based learning. This problem analyzes the perceptions of MTs Mambaul Ihsan teachers towards digital literacy and its relation to future educational challenges; describes the teachers' experiences in implementing digital literacy in learning; and examines the planning and strategies for developing digital literacy carried out by teachers. The results indicate that there are two groups of teachers: those who have been able to utilize technology creatively and effectively in their learning, and those who still face structural and technical barriers in implementing digital literacy. Furthermore, a dynamic emerged between the use of technology and efforts to maintain religious values ??in the learning process. The findings of this study emphasize the importance of improving contextual digital literacy training, strengthening infrastructure support, and developing policies that encourage the integration of technology with Islamic educational values. Thus, teachers' digital literacy is expected to become a key foundation for building adaptive, innovative, and character-based education in the future.